Exploring the musicalization of texts in gregorian chant using data analytics (2020)
Applying an algorithm for local sequence alignment in the DNA to 1,273 chants organized in pairs, a similarity percent of its texts and melodies was obtained. This generated 68,810,000 records. Using Descriptive Analytics, we conclude: in punctuation marks the sound duration is lengthened, stop words are musicalized using few pitches, semantic of text do not determine always how to musicalize it, the centonization process was influenced by the chant type and ethos (mode) reusing mostly phrases. These conclusions help to perform and musicalize latin texts for the Proper of the Mass. Finally, a future work in digital humanities is proposed.